METHODS AND MEANS OF INFORMATION AND ADVERTISING ACTIVITIES OF UNIVERSITY DEPARTMENTS IN SOCIAL INTERNET ENVIRONMENTS - TRACH, Olha (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Today, all advertising activities are moving to the social media of the Internet. The period of the covid-19 pandemic and the martial law in Ukraine accelerated this process. Now it is difficult to avoid that something cannot be found on the Internet. Institutions of higher education are no exception. Universities and their divisional divisions also need promotional activities to attract applicants and branding through the social media of the Internet. Attracting applicants by informing them about university departments is a career guidance activity. With the advent of distance learning, informational and advertising activities of higher education institutions in social networks began to gain popularity, in particular, for career guidance purposes. In order to carry out informational and advertising activities of university units in the social environment of the Internet, it is necessary to create an informational image. The creation of an informational image of university units is done by creating official pages in social networks. The most popular social networks for creating an informational image of the university's divisions in the social environments of the Internet are Facebook, Instagram, and Telegram. The article develops a formal model of the information image of units of a higher education institution. The requirements for the pages of higher education institutions and their departments are different from ordinary pages for goods or services, given their specificity and target audience. Therefore, the requirements for creating pages of university divisions in social networks are as follows: logo of the division, name of the division page with affiliation to the institution of higher education, information about the division ("cap" of the profile) with the following data: page name, name of the division, abbreviation of the institute/university, university affiliation, website of the unit, address of the unit, telephone. The article describes the stages of maintaining a career guidance activity page. The list of elements that are part of the career guidance topic of the post has been defined: the name of the specialty; the name of the department that trains specialists in the chosen specialty; terms of study; form of education; cost of education; contact information of the department; license volume. The tools and methods of information and advertising activities of departments of higher education institutions presented in the work were implemented at the Department of Social Communications and Information Activities of Lviv Polytechnic National University for three years.
Keywords: virtual communities; web projects; career guidance activities; HEI